Explaining Variations in Long-term Care Use and Expenditures Under the Public Long-term Care Insurance Systems: A Case Study Comparison of Korea and Japan - Hongsoo Kim; Nan-He Yoon; Youjin Hahn; Hideki Hashimoto (Kerman University of Medical Sciences, 2023)
Background  Establishing universal coverage of formal long-term care (LTC) services is an urgent policy need for aging populations that requires efficient management of quality and financing. Although current variation in LTC service use between and within countries suggests the potential for improvement by efficient management, this topic remains underexamined. We aimed to identify the sources of variance in LTC use and expenditures through a unique crosscountry comparison of Japan and South Korea, which have formal public LTC insurance (LTCI) schemes that are analogous but have unique operational and demographic structures. Methods  Taking administrative regions as the unit of analysis, we assembled data on the LTC utilization rate of people aged ≥65 years, and expenditures per recipient from 2013 to 2015 as the outcome variables. Explanatory variables included demand-related factors, such as regional demographic and economic conditions, and supply characteristics derived from existing public databases. We conducted weighted least squares regression with fixed effects for the pooled data and used Blinder-Oaxaca decomposition to identify sources of outcome variance between the two countries. Results  The average LTC utilization rate was 6.8% in Korea and 18.2% in Japan. Expenditures per recipient were approximately 1.4 times higher in Japan than in Korea. The difference in the utilization rate was mostly explained by between-country differences in supply- and demand-related factors, whereas the difference in expenditures per recipient was largely attributed to unobserved country-specific factors. Conclusion  The current findings suggest that LTC utilization is determined largely by the demographic and functional characteristics of older people, whereas expenditures are more likely affected by institutional factors such as the insurance governance scheme and the policy choice of the target population segment and coverage. The results suggest that strategic choice of LTC institutional schemes is required to ensure financial sustainability to meet changing demands caused by population aging.